"A Viable Path for Education"—Indigenous-Language Immersion and Sustainable Self-Determination. Issue 5 (3rd September 2021) - McCarty, Teresa L.; Noguera, Joaquín; Lee, Tiffany S.; Nicholas, Sheilah E.
ABSTRACT: This article examines Indigenous-language immersion (ILI) schooling, an innovative approach in which most or all instruction occurs in the Indigenous language, with a strong culture-based curriculum. With the goals of promoting language revitalization, academic/holistic wellbeing, and cultural identity and continuance, ILI is a form of sustainable self-determination. We ground our analysis in a growing body of ILI scholarship and preliminary findings from our research in a mixed-method, multisite, US-wide study of ILI schooling. The study asks: What can ILI teach us to improve education practice for Native American learners? How can such a study inform research, theory, practice, and policy for Indigenous and other minoritized learners? We begin with a brief history of ILI movements in the US and then discuss ILI's de/anticolonial aims, highlighting connections to sustainable self-determination. We illustrate these processes with examples of pedagogical, communal, and nation-building goals and practices evident in our national study. We conclude with the broader implications of ILI as a "viable path for education" for sustainable enactments of Indigenous self-determination.